Committing to grow: Privatizations and firm dynamics in East Germany - Ufuk Akcigit; Harun Alp; André Diegmann; Nicolas Serrano-Velarde (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper investigates a unique policy designed to maintain employment during the privatization of East German firms after the fall of the Iron Curtain. The policy required new owners of the firms to commit to employment targets, with penalties for non-compliance. Using a dynamic model, we highlight three channels through which employment targets impact firms: distorted employment decisions, increased productivity, and higher exit rates. Our empirical analysis, using a novel dataset and instrumental variable approach, confirms these findings. We estimate a 22% points higher annual employment growth rate, a 14% points higher annual productivity growth, and a 3.6% points higher probability of exit for firms with binding employment targets. Our calibrated model further demonstrates that without these targets, aggregate employment would have been 15% lower after 10 years. Additionally, an alternative policy of productivity investment subsidies proved costly and less effective in the short term.
Keywords: D22; D24; J08; L25; 330; industrial policy; privatizations; productivity; size-dependent regulations